RANGKAIAN CASCADE PADA RANGKAIAN SEQUENTIAL ASINKRON - T.S., Kuat Rahardjo (Jurnal Teknik Elektro, 2001)
Cascade circuit is once of methode to simplify digital circuit design, because its reducing thenumber of input in every part of cascade circuit. Usually, the design methode is apllied incombinational circuit design. This design methode can be implement too in synchronoussequential circuit, usually for counter circuit design. But in the asynchronous sequential, thisdesign methode is very rare to applied. This article is discussing only for cascade circuitdesign methode in asynchronous sequential mode, using âMaster Quizâ case study todescribe thisKeyword: Rangkaian CASCADE pada SEQUENTIAL ASINKRON, untuk merancangrangkaian cepat tepat dengan jumlah regu banyak.